Root and Eruption Defects in c-Fos Mice Are Driven by Loss of Osteoclasts. (December 2015) - Alfaqeeh, S.; Oralova, V.; Foxworthy, M.; Matalova, E.; Grigoriadis, A.E.; Tucker, A.S.
C-Fos homozygous mice lack osteoclasts with a failure of the teeth to erupt and with an arrest of root development. Here, we characterize the defects associated with the failure in root development and the loss of the tooth-bone interface, and we investigate the underlying causes. We show that, while homozygous c-Fos mice have no multinucleated osteoclasts, heterozygous mice have a reduction in the number of osteoclasts with a reduction in the tooth-bone interface during development and subtle skeletal defects postnatally. In the homozygous mutants bone is found to penetrate the tooth, particularly at the apical end, physically disrupting the root forming HERS (Hertwig's epithelial root sheath) cells. The cells of the HERS continue to proliferate but cannot extend downward due to the presence of bone, leading to a loss of root formation. Tooth germ culture showed that the developing tooth invaded the static bone in mutant tissue, rather than the bone encroaching on the tooth. Although c-Fos has been shown to be expressed in developing teeth, the defect in maintenance of the tooth-bone interface appears to be driven solely by the lack of osteoclasts, as this defect can be rescued in the presence of donor osteoclasts. The rescue suggests that signals from the tooth recruit osteoclasts to clear the bone from around the tooth, allowing the tooth to grow, form roots, and later erupt.